Pengaruh Penerapan E-Filing Dan Pengetahuan Perpajakan Terhadap Kepatuhan Wajib Pajak Dengan Biaya Kepatuhan Sebagai Variabel Moderasi - M. Ardhy Erwanda; Henri Agustin; Erly Mulyani (Universitas Negeri Padang, 2019)
This study aims to determine the effect of applying e-filing and knowledge of taxation on taxpayer compliance. Compliance costs as moderating variable that moderate relations between application e-filing and knowledge taxation on the taxpayer compliance. The population in this study is taxpayers in Padang city. The number off samples used was 100 respondents with the sampling method using purposive sampling. The data used in this study are primary data. Data collection techniques are done by questionnaire. The data analysis technique used is multiple regression and moderated regression analysis. The results obtained are the application of e-filing has a significant positive effect on taxpayer compliance, knowledge of taxation does not affect taxpayer compliance, compliance costs proved to moderate the relationship between the implementation of e-filing and taxpayer compliance, and the cost of compliance was not proven to moderate the knowledge relationship of taxation with taxpayer compliance